Challenges for Educators in the Digital Era and Educators' Strategies in Improving Professionalism and Careers - Abdul Rahman Hidayat; Nanda Apridina Nurhaliza (al-Afkar, Journal For Islamic Studies, 2025)
The digital age presents complex challenges for educators, including the need to master new technologies and adapt teaching methods. Educators must face changes in the curriculum and increasing societal expectations for educational outcomes. To overcome these challenges, professionalism and career improvement strategies are very important. Educators need to carry out self-development through continuous training, getting involved in teacher organizations and taking part in PPG. With this approach, educators can face challenges in the digital era and can improve the quality of teaching in line with current developments.